Conference on agricultural sustainability, growth, and poverty alleviation in East and Southeast Asia - Witcover, Julie; Rosegrant, Mark W. (International Food Policy Research Institute, 1995)
This first in a series of regional conferences on this subject brought together more than fifty agricultural scientists and policymakers from China, Indonesia, Malaysia, the Philippines, Thailand, Vietnam, and from international agricultural research centers and the Asian Development Bank to discuss how best to promote sustainable agricultural intensification--natural resource management that safeguards productivity of the natural resource base while meeting economic growth and poverty alleviation objectives... What are the ingredients for success in bringing natural resource management into the set of objectives for policymakers and researchers? Conference participants brought a range of country experiences and policy and research perspectives--different economic development paths; different government roles in shaping those strategies; different institutions and mechanisms for government planning; different population densities, country sizes, natural resource richness, and level of food security--to the table for four days in grappling with this question. In the process of taking into consideration actors other than the government, levels other than the national, and mechanisms through which effective institutional links can be forged, the participants did not always reach consensus. Their debate, however, brought to light major issues to be researched and resolved along the way to "sustainable intensification."